Preoperative Anxiety and Depression Are Associated with Lateral Compartment Osteoarthritis Progression After Medial Unicompartmental Knee Arthroplasty: A Retrospective Observational Cohort Study - Zheng Wang; Mincong Du; Zheng Li; Shuai An; Guanglei Cao; Ye Huang (Journal of Clinical Medicine, 2026)
Background: This study aimed to evaluate whether preoperative anxiety and/or depression (AD) is associated with mid-term lateral compartment osteoarthritis progression (LOP) after medial unicompartmental knee arthroplasty (mUKA). Methods: This retrospective observational cohort study analyzed a prospectively maintained institutional database of consecutive patients who underwent mUKA between March 2016 and December 2020. Preoperative psychological status was assessed using the Hospital Anxiety and Depression Scale (HADS); patients with subscore ≥8 were categorized as having AD. Clinical outcomes included Oxford Knee Score (OKS), Forgotten Joint Score (FJS), Kujala score, and complications at a mean follow-up of 70 months. Serial full-length standing radiographs were used to measure coronal alignment and Kellgren–Lawrence (K/L) grade in the lateral compartment. LOP was defined as an increase of ≥1 K/L grade between the early postoperative and final follow-up radiographs. Univariate and multivariable logistic regression were used to identify factors associated with LOP. Results: A total of 203 knees met the inclusion criteria; 26 knees were classified into the AD group and 177 into the Non-AD group. At final follow-up, the AD group had worse OKS, smaller OKS improvement, and lower FJS and Kujala scores. Radiographic follow-up was available in 99 knees. LOP occurred in 26.3% of knees overall. The rate of LOP was significantly higher in the AD group than in the Non-AD group (60.0% vs. 20.2%). In univariate analysis, AD was associated with LOP. In multivariable logistic regression, preoperative AD remained associated with a higher likelihood of LOP after adjustment for prespecified covariates. Conclusions: Preoperative anxiety and/or depression was associated with a higher frequency of radiographic lateral compartment osteoarthritis progression and worse mid-term patient-reported outcomes after mUKA. These findings should be considered exploratory and hypothesis-generating.